Tolvaptan and its potential in the treatment of hyponatremia - Y Howard Lien; Megan B Dixon (Dove Medical Press, 2008)
Megan B Dixon, Y Howard LienDepartment of Medicine, University of Arizona, Arizona Kidney Disease and Hypertension Center, Tucson, Arizona, USAAbstract: Tolvaptan is a selective arginine vasopressin (AVP) V2 receptor blocker used to induce free water diuresis in the treatment of euvolemic or hypervolemic hyponatremia. Currently the orally active medication is in the final stages prior to approval by the FDA for outpatient therapy. It appears to be safe and effective at promoting aquaresis and raising serum sodium levels in both short- and long-term studies. Tolvaptan is also effective for treatment of congestive heart failure (CHF) exacerbation, but whether there are long standing beneficial effects on CHF is still controversial. Prolonged use of tolvaptan leads to increased endogenous levels of AVP and perhaps over-stimulation of V1A receptors. Theoretically this activation could lead to increased afterload and cardiac myocyte fibrosis, causing progression of CHF. However, after 52 weeks of tolvaptan therapy there was no worsening of left ventricular dilatation. In addition, tolvaptan is metabolized by the CYP3A4 system; thus physicians should be aware of the potential for increased interactions with other medications. Tolvaptan is a breakthrough in the therapy of hyponatremia as it directly combats elevated AVP levels associated with the syndrome of inappropriate secretion of antidiuretic hormone, congestive heart failure, and cirrhosis of the liver.Keywords: hyponatremia, arginine vasopressin, vasopressin receptors, syndrome of inappropriate antidiuretic hormone, congestive heart failure, liver cirrhosis